An Effective GTO Algorithm-Based Cost-Benefit Analysis of DISCOs by Optimal Allocation of DG and DSTATCOM in a Radial Distribution Network - RAM PRASAD KANNEMADUGU; V. Adhimoorthy; A. Lakshmi Devi (ITEGAM-JETIA)
Electric power Distribution Companies (DISCOs) is playing a major role for delivering active power from distribution substations to customers with lover cost, high reliability and voltage stability. In the DICOs, the transmission lines are redial in nature; all buses are containing the load and no generating buses. Therefore, voltage at each bus is minimized, loss of the network and voltage deviation is increased, and cost and benefit of the DISCOs and consumers are minimized. This paper maximizes the cost–benefit, and voltage stability of DISCOs is improved by optimally considering the Distributed Generation (DGs) and DSTATCOM. Here, applied a novel comprehensive Group Teaching Optimization (GTO) algorithm for planning DG units and DSTATCOM which considers both the Distribution Company’s and the DG Owner’s (DGO) profits simultaneously. The proposed GTO is applied to a 33-node test system and simulations are carried out using MATLAB platform and results show the applicability of the GTO in the DISCOs.